The attitude of the teachers towards the practice of streaming - Walugembe, Josephine Vuyelwa (My University, 2018)
Differentiation, as a strategy within inclusive education, seeks to respond to the challenges and opportunities of diversity within classrooms. This is done by adapting and modifying the methods of instruction, curriculum and activities to address effectively the needs and the potential of diverse learners. In the light of this, many teachers believe streaming is a form of differentiation, and a way to respond to the diversity faced in the classroom. To investigate this situation, this study explored the extent to which the attitudes of teachers sustained the practice of streaming in secondary schools. It also assessed whether the practice of streaming was congruent with the principles of inclusive education. Streaming is the practice of separating learners based on their respective cognitive abilities and their placement in similar ability groups. By using a qualitative research approach, this study found that teachers believed that streaming enabled differentiation and effective classroom management strategies. The various attitudes of teachers showed that they assumed streaming helped to deal with the distinguishable differences in learners’ ability, their conduct and their perceived ability to cope with the curriculum demands. However, there was a misalignment between how streaming was practised and the principles of inclusive education. A fundamental issue was that those learners who were placed in the lower-ability groups were labelled negatively, and there was no differentiation that occurred within similar ability classes. In effect, streaming became a selffulfilling prophecy for those in the lower-ability groups.
A research report submitted to the Wits School of Education, Faculty of Humanities, University of Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Education by combination of coursework and research. Johannesburg 2018
Keywords: Multicultural education; Inclusive education--South Africa